EPIDEMOLOGY OF TRAUMA GLOBALY - Yuniarti, Nur (E-Jurnal Medika Udayana; vol 2 no 10 (2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 This study describes the epidemiology of trauma globaly. Trauma can cause death, burden of disease and economic losses. Traffic accidents are the most common cause of injury in the whole world. Riskesdes 2007, the proportion of the highest injury of Yogyakarta, experienced by adult age group, higher in male, the high levels of injury increasing the proportion of respondents. Found in the work as an employee, in the upper midle economic level. Lower limb (leg) is part most affected by injuries. Based on the types of injuries classified as serious in a row that a head injury. Traffic accidents are often caused by four factors: road user, drivers, pedestrian, and vehicle. Because the victim of traffic accident is quite high and high health costs incurred . By him that there are three phases of stage traffic accident prevention, the prevention of the pre-crash phase, the phase of the accident, when the accident occur, to minimize the injuries. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Injury, Accident, Epidemology